Mechanisms of Cancer Inhibition by Local Anesthetics - Zhang, Yiguo; Jing, Yixin; Pan, Rui; Ding, Ke; Chen, Rong; Meng, Qingtao (Frontiers in Pharmacology, 2021)
Surgery using local anesthetics is a key part of cancer management. Local anesthetics may directly or indirectly affect tumor progression. In vitro and in vivo studies demonstrated that local anesthetics reduced cancer recurrence. The etiology of this effect is likely multifactorial. Numerous mechanisms were proposed based on the local anesthetic used and the type of cancer. Mechanisms center on NaV1.5 channels, Ras homolog gene family member A, cell cycle, endothelial growth factor receptor, calcium Influx, microRNA and mitochondrial, in combination with hyperthermia and transient receptor potential melastatin 7 channels. Local anesthetics significantly decrease the proliferation of cancers, including ovarian, breast, prostate, thyroid, colon, glioma, and histiocytic lymphoma cell cancers, by activating cell death signaling and decreasing survival pathways. We also summarized clinical evidence and randomized trial data to confirm that local anesthetics inhibited tumor progression.